KAJIAN TEKNIS PERENCANAAN KORIDOR JALAN PANDANARAN SEMARANG - -, Diharto (Semarang State University, 2010)
Pandanaran Road is one of corridor the golden triangle area of trade and services the city of Semarang, is a road that is quite important as a connecting node Simpang Lima and node Tugu Muda. The problems that occurred in the corridor Street Pandanaran including: the high intensity of traffic disrupt the ease and convenience of pedestrians, lack of greenery and arrangement of green belt, Cadger are concentrated at the center by-by, wide walkways between 2.1 - 3.8 m, and yet the (gate) Pandanaran Road corridor with the Simpang Lima area and Tugu Muda. The concept of using a futuristic design, green building architecture, and sustainable. Design approach based on the Regulation of the Director General of Highways, reviews building and environmental planning Regions Simpang Lima Semarang City, and field measurement. The result of the design is the arrangement of roads 14 m wide (four-lane two-way), 2 m road shoulder (as a bike path), the arrangement of pedestrian width 3 m, the addition of greenery, the addition of pedestrian lighting, street lighting additions, adding bookmarks, adding the sitting group , The arrangement of the panel box, and the gate area.Jalan Pandanaran merupakan salah satu koridor kawasan segitiga emas perdagangan dan jasa Kota Semarang, merupakan jalan yang cukup penting sebagai menghubungkan simpul Simpang Lima dan simpul Tugu Muda. Permasalahan yang terjadi di koridor Jalan Pandanaran diantaranya : tingginya intensitas lalu lintas mengganggu kemudahan dan kenyamanan pejalan kaki, kurangnya penghijauan dan penataan jalur hijau, Pedagang Kaki Lima terkonsentrasi di depan pusat oleh-oleh, lebar jalur pejalan kaki antara 2,1 - 3,8 m, dan belum adanya (gerbang) koridor Jalan Pandanaran dengan kawasan Simpang Lima dan Tugu Muda. Konsep desainnya menggunakan futuristik, green building architecture, dan sustainable. Pendekatan desain mengacu pada Peraturan Direktur Jenderal Bina Marga, review Rencana Tata Bangunan dan Lingkungan Kawasan Simpang Lima Kota Semarang, dan pengukuran lapangan. Hasil desain adalah penataan lebar jalan 14 m (empat lajur dua arah), bahu jalan 2 m (sebagai jalur sepeda), penataan lebar pejalan kaki 3 m, penambahan penghijauan, penambahan lampu pedestrian, penambahan lampu penerangan jalan, penambahan penanda, penambahan sitting group, penataan box panel, dan gerbang kawasan.